Effect of Pressure Dependent Viscosity on Couple Stress Squeeze Film Lubrication between Rough Parallel Plates - Neminath Bujappa Naduvinamani (Japanese Society of Tribologists, 2015)
In this paper, a theoretical study of the effect of pressure dependent viscosity on couple stress squeeze film lubrication between rough parallel plates is analyzed on the basis of Barus experimental results. Stokes micro continuum theory of couple stress fluids and Christensen’s stochastic theory for the lubrication of rough surfaces have been used for the derivation of generalized stochastic Reynold’s type equation with pressure dependent viscosity. In the context of Christensen’s theory, the two types of one dimensional roughness (Longitudinal and transverse) patterns are considered. Expressions for the squeeze film pressure, the load carrying capacity and time-height relations are obtained. It is found that, the effect of roughness parameter is to increase (decrease) the load carrying capacity and the response time for transverse (longitudinal) roughness patterns as compared to the smooth case. Further the effect of pressure dependent viscosity variation is to reduce the load carrying capacity and squeeze film time as compared to the constant viscosity case.